Status of Women Employees and Job Satisfaction of Women Working in Corporate Sector - Kaang , Sugandha Kohli (Gyan Management Journal, 2024)
The present paper examines the level of job satisfaction working in the corporate sector in the region of Gurgaon and Chandigarh. The major findings of the study are that women are entering the corporate sector in high numbers however their proportion is still less vis a vis their male counterparts. In the present study, majority of the women were found to be dissatisfied with their present jobs. There were many reasons for dissatisfaction among the respondents. Out of which mainly were heavy work load, long working hours, biased promotion policies and unequal pay. Further, it was observed that unseen barriers are quite prevalent in the corporate world due to which women are not able to reach at the top managerial positions. These barriers are prevalent due to the misconceptions created in respect of the ability and potential of women employees. This patriarchal mindset of the people working in corporate sector is the major hindrance in their growth and progress.